Solubility Enhancement of Nateglinide by Solid Dispersion and Their Characterization - PRAVALLIKA, GOUNIKADI SAI; RAMESH, K.; KUMAR, G.VIJAY (International Journal of Pharmacy Research & Technology (IJPRT), 2023)
The aim of the present work is to investigate the possibility of obtaining immediate release tablet of Nateglinide with improved dissolution using Solid dispersion technique. The solubility and dissolution rate of Nateglinide can be enhanced by formulating SDs of Nateglinide with PEG 6000.The solubilization effect of PEG 6000, reduction of particle aggregation of the drug, formation of microcrystalline or amorphous drug, increased wetability and dispersibility, and alteration of the surface properties of the drug particles might be responsible for the enhanced solubility and dissolution rate of Nateglinide from its SD and to some extent in PMs. No endothermic peak of Nateglinide was present in of SDs with PEG 6000 suggesting the absence of crystalline Nateglinide. From FTIR spectroscopy, it was concluded that there was no well defined chemical interaction between Nateglinide and PEG 6000 in SDs and in PMs, as no important new peaks could be observed. The identical composition of Superdisintegrants showed that a substantial shorter time require for disintegration can be obtained and immediate release tablet were prepared. The Nateglinide immediate release tablet (F2) showed 78.72% drug release within first 5 min. and 99.50% drug release with in 30 min. The results showed that the formulation satisfied the objective of fast disintegration, dissolution, % friability, hardness, wetting time, water absorption ratio, ease of administration and safety. Success of the present study recommends a detailed investigation in to in-vivo studies for its effective use in clinical practice.